Choice of Law and Forum Clauses in Shipping Documents — Revising Section 11 of the Carriage of Goods by Sea Act 1991 (Cth) - Allison, Simon (2014)
Since 1904, Australia has sought to protect shippers by prohibiting parties to contracts such as bills of lading from contracting out of Australian law and jurisdiction. Today, this protection lives on in s 11 of the Carriage of Goods by Sea Act 1991 (Cth). This section has recently been in the spotlight following a divergence of authority relating to its scope. This article argues that legislative revision of s 11 is necessary in order to clarify its scope and to ensure that its operation is consistent with the underlying policies justifying its existence, as expressed by the legislature.